Library Service Innovation in The Department of Archives and Library of Bandung District - Diva Thea Theodora Ismail; Rosiana Nurwa Indah; Rifqi Zaeni Achmad Syam (Universitas Terbuka, 2021)
The Bandung Regency Archives and Libraries Service is one of the regional public libraries of Bandung Regency which has service innovations during the COVID-19 pandemic. The Bandung Regency Archives and Library Service provides a mobile user interface service named i-Sabilulungan. The purpose of this study was to determine the usefulness of the i-Sabilulungan application as a service innovation during the COVID-19 pandemic at the Bandung Regency Archives and Library Service. The research method used in this research is descriptive qualitative research method with data collection techniques through observation and interviews. In this study, the informants were librarians managing the i-Sabilulungan mobile application. The results of this study reveal that i-Sabilulungan as a library service innovation for the Bandung Regency Archives and Libraries Service has fulfilled an important element in the application of the mobile user interface application. The i-Sabilulungan application has fulfilled 10 elements of the application of the mobile user interface application which consists of several elements including connectivity, simplicity, directional, informative, interactivity, user friendliness, comprehensiveness (completeness), continuity (sustainable), personalization (personalization) and internal elements (internal).